KONSEP PEMAHAMAN AQIDAH KHAWARIJ DARI ZAMAN KE ZAMAN (Maslahah: Journal of Islamic Studies, 2023)
The relationship between Dzul Khuwaishirah and the people who carried out the rebellionagainst Uthman, and the Khawarij who rebelled against Ali bin Abi Talib because of theAt-Tahkim incident, is indeed very clear and visible. However, the term Khawarij is onlyappropriate for people who rebel against Ali bin Abi Talib because of the At-Tahkimincident, on the grounds that they exist as a group of people who form a group that has apolitical orientation and separate views that have had an influence on the matter ofthought and belief in real terms, the opposite of the previous circumstances.
Keywords: Aqidah; Khawarij; Age